1979
DOI: 10.1139/y79-124
|View full text |Cite
|
Sign up to set email alerts
|

Calcium antagonists and contractile responses in rat vas deferens and guinea pig ileal smooth muscle

Abstract: The effect of depletion of extracellular Ca2+ (Ca2+ext) on the loss of responsiveness of the guinea pig ileal longitudinal muscle (g.p.i.l.m.) and the rat vas deferens (r.v.d.) to K+ and cis-2-methyl-4-dimethylaminomethyl-1,3-dioxolane methiodide (CD), and K+ and noradrenaline (NA), has been examined and compared with the effects of a variety of local anesthetics and calcium antagonists. The results indicate that qualitative similarities are apparent with respect to the dependence of agonist-induced activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 0 publications
6
23
0
Order By: Relevance
“…Components ofthe KCI response resistant to Ca2" deprivation In agreement with Swamy et al (1976), Triggle et al (1979) and Shimodan & Sunano (1981), we have found that lanthanum, verapamil and methoxyverapamil completely block KCI contractions. Since it is well established that these drugs inhibit the movement of Ca2" into smooth muscle, this is strong evidence that both phases of the KCI contraction in the rat vas deferens use extracellular Ca2+.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Components ofthe KCI response resistant to Ca2" deprivation In agreement with Swamy et al (1976), Triggle et al (1979) and Shimodan & Sunano (1981), we have found that lanthanum, verapamil and methoxyverapamil completely block KCI contractions. Since it is well established that these drugs inhibit the movement of Ca2" into smooth muscle, this is strong evidence that both phases of the KCI contraction in the rat vas deferens use extracellular Ca2+.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, the rise in tension is maintained at a lower level (tonic response) intracellular cation concentration produced by any of (Shimodan & Sunano, 1981). These responses are these processes may secondarily mobilize intracelluantagonized by calcium-free conditions, by lanthlar calcium stores (Bolton, 1979 nifedipine, verapamil and methoxyverapamil (Swamy, Triggle & Triggle 1976;Triggle, Swamy & Triggle, 1979;Shimodan & Sunano, 1981). These results show that in the vas deferens, K+ primarily utilizes extracellular calcium for contraction.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, a-adrenoceptor agonists induce rhythmic activity in human vasa deferentia (Ratnasooriya, Wadsworth & Gilmore, 1979), present in both longitudinal and circular muscle layers (Anton & McGrath, 1977). Although analysis of the biphasic response to high concentrations of noradrenaline in the rat vas deferens has been performed, involving Ca2l-deprivation studies and the use of La3" and calcium channel inhibitors (Swamy, Triggle & Triggle, 1976;Triggle, Swamy & Triggle, 1979;Stone, 1981;Hay & Wadsworth, 1983b), there have been no investigations into the involvement of Ca2+ in the rhythmic contractions produced by a-adrenoceptor stimulation. Thus, the purpose of this study was to examine excitationcontraction coupling mechanisms involved in rhythmic activity in the rat vas deferens, using calcium channel inhibitors and analysis of the Ca2+-dependence of the responses.…”
Section: Introductionmentioning
confidence: 99%
“…Receptor-mediated Ca 2+ influx has been demonstrated in many tissues and cells, but in some tissues, agonist-induced Ca 2+ influx is sensitive to voltage-dependent Ca2+ channel blockers (8,9,13), whereas in others, it is not (14,15). These findings suggest that these channels are tissue-specific (16).…”
mentioning
confidence: 93%
“…However, the dose-response curve for IP3 formation does not coincide with that for muscle contraction, the latter being in a lower concentration range of CCh (7). Moreover, contraction of ileal longitudinal muscle is known mainly to depend on the extracellular Ca 2+ concentration (8). These facts indicate that not only release from intracellular stores, but also influx of extracellular Ca 2+ through the receptor-operated Ca 2+ channels may con tribute to the increase in [Ca 2+]; in longitudi nal ileal smooth muscle.…”
mentioning
confidence: 96%